The phantasmagoria: From ghostly apparitions to multisensory fairground entertainment - Spence, Charles (Frontiers in Communication, 2022)
The ‘phantasmagoria’ is a term that originally referred to the ghost lantern shows first staged in France at the end of the 18th Century by the Belgian inventor and entertainer Étienne-Gaspard Robertson. The question to be addressed in this review concerns the link between the phantasmagoria (defined as a ghostly visual entertainment) and the multisensory sensorium (or sensory overload) of the fairground and even, in several other cases, the Gesamtkunstwerk (the German term for ‘the total work of art’). I would like to suggest that the missing link may involve the ghost attractions, such as Dr. Pepper’s Ghost (first developed at the Royal Polytechnic Institute in London in the 1860s), and the Phantasmagoria, that were both promoted in fairgrounds across England in the closing decades of the 19th Century.